Analisis Pengaruh Service Quality dan Biaya Terhadap Kepuasan pelanggan (Study Kasus Pada PT. Mustikasakti Sarana Kencana) - Ivan Reyhansyah (Sekolah Tinggi Maritim Yogyakarta, 2020)
The aim study to analize influence service quality to customer satisfaction on PT. Mustikasakti Sarana Kencana. Method use by corelation, data collecting by survey on 49 respondent. The result point out that service quality influenced to customer satisfaction, then customer satisfaction influenced to customer loyalty. tant, spesific, or representative for the article.